Entrepreneurial Resiliency Among Indigenous Women Entrepreneurs in Papua Pegunungan: The Role of Digital Literacy and Dynamic Capability - Nanang Gunawan; Ayu Anggraini Tambunan; Defran Siska; Anike Amidek Ikinia (Universitas Sebelas Maret, 2026)
This study investigates the entrepreneurial resiliency of indigenous women entrepreneurs in Papua Pegunungan, examining how digital literacy and dynamic capability jointly shape their capacity to adapt within a structurally constrained, geographically isolated environment. Resilience is treated not as a fixed trait but as a socio-technical process that unfolds through engagement with digital tools and context-specific innovation. The study tests whether dynamic capability channels the influence of digital literacy on entrepreneurial resiliency, drawing on survey data from 181 respondents analyzed through partial least squares structural equation modeling (PLS-SEM). Contrary to a simple full-mediation account, the results show that digital literacy exerts a strong, statistically significant direct effect on entrepreneurial resiliency (β = 0.697) that considerably outweighs the indirect route running through dynamic capability (β = 0.126), signaling partial rather than full mediation. Digital tools therefore contribute to resiliency both on their own and by strengthening the capacity to sense, seize, and reconfigure resources, although the direct pathway dominates. These findings position entrepreneurial resiliency among indigenous women in Papua Pegunungan as a context-driven construct shaped by informal learning, ecological awareness, and adaptive routines, and they challenge deficit-based narratives by foregrounding the strategic agency of marginalized entrepreneurs. The findings point to a need for localized digital-training and capability-building programs that remain attentive to cultural and ecological realities.Keywords: dani ethnic community; ecological embeddedness; informal learning; marginalized entrepreneurship; partial least squares structural equation modeling; socio-technical adaptation